Microscopy-based phenotypic profiling of infection by Staphylococcus aureus clinical isolates reveals intracellular lifestyle as a prevalent feature - Lopes, Ines Rodrigues (2022)
Staphylococcus aureus is increasingly recognized as a facultative intracellular pathogen, although the significance and pervasiveness of its intracellular lifestyle remain controversial. Here, we applied fluorescence microscopy-based infection assays and automated image analysis to profile the interaction of 191 S. aureus isolates from patients with bone/joint infections, bacteremia, and infective endocarditis, with four host cell types, at five times post-infection. This multiparametric analysis revealed that almost all isolates are internalized and that a large fraction replicate and persist within host cells, presenting distinct infection profiles in non-professional vs. professional phagocytes. Phenotypic clustering highlighted interesting sub-groups, including one comprising isolates exhibiting high intracellular replication and inducing delayed host death in vitro and in vivo. These isolates are deficient for the cysteine protease staphopain A. This study establishes S. aureus intracellular lifestyle as a prevalent feature of infection, with potential implications for the effective treatment of staphylococcal infections.